Pengaruh Liputan Media Terhadap Efisiensi Investasi Pada Perusahaan Non Keuangan dalam Perspektif Syariah - Selvina, Mia; Aulia, Darlin (Universitas Islam Negeri Raden Intan, 2022)
This study examines the effect of media coverage on investment efficiency in non-financial companies that trade products according to Islamic law listed in the 2003 DSN-MUI article 3 paragraph 2. Media coverage reduces underinvestment but increases overinvestment. The negative effects of media coverage of under-investment are more pronounced in firms influenced by greater information asymmetry and poorer corporate governance. The positive effect of media coverage on overinvestment is driven by media-driven CEO overconfidence. Additional results show that both in general, higher news optimism is associated with less investment but more investment. In addition, media coverage influences investment efficiency through its information dissemination rather than its information generation function. Collectively, the results of this study indicate that corporate media promotes more investment (overinvestment) than underinvestment (underinvestment).